Successful research projects a guide for postgraduates - Lee, Anne (Routledge, 2020)
"Comprehensive and accessible, this guide is the perfect companion for the busy student facing their postgraduate research project. It covers the key questions, challenges and solutions including: how to organise time most effectively; how to work with colleagues; how to stay motivated and how to get the best out of a supervisor. By providing the reader with the significant theories behind ways of managing projects, identifying important goals and solving problems, Manging your Research Project provides models for good research and writing processes as well as key practical tips within each chapter"--Provided by publisher.